Creating Vidant Health's Healthy Food Environment - Gaskins, Scottie; Kolasa, Kathryn M.; Simmons, Rose Ann; Njuguna, Njeri; White, Andy (My University, 2013)
The paper describes the journey taken by Vidant Health (formerly University Health Systems of Eastern Carolina) to create a healthy eating environmnet on its entire campus. Vidant Health was among the first hospitals in the country to have a policy that defines percentages of foods that need to meet a healthy criteria. They also employed price leveraging to increase the purchase of healthy options.
Keywords: Food; Environments; Policies; Changes; Healthy; Eating; Worksites; Wellness